Africaines African Women/ (3EaQjbjGJs - Aminata Djegal; Angele Ettoundi Essamba; Christine Eyene; Hala el Koussy; Larissa Hoops; Maggie Otieno; Malala Andiralavidrazana; Nadira Laggoune-Aklouche; Sokari Douglas Camp; Susan Hefuna; Sithabile Mlotshwa, Michele Magema, Aza Monsongui, Nadia Kaabi Linke, Mouna Jemal, Marianne Catzaras, Gbaguidi Pelagie, Amina Menia, Katia Kameli, Fatima Chafaa, Kheira Slimani, Rahmoune Thileli, Elyasmine Hocine, Feriel Benmbarek, Berni Searle (Algiers; Musee National d'Art Moderne & Contemporanea, 2009)
Exhibition catalog. Texts: Nadira Laggoune-Aklouche (curator); Christine Eyene. Artists: Sokari Douglas Camp, Hala el Koussy, Susan Hefuna, Malala Andiralavidrazana, Larissa Hoops, Maggie Otieno, Angele Ettoundi Essamba, Aminata Djegal, Sithabile Mlotshwa, Michele Magema, Aza Monsongui, Nadia Kaabi Linke, Mouna Jemal, Marianne Catzaras, Gbaguidi Pelagie, Amina Menia, Katia Kameli, Fatima Chafaa, Kheira Slimani, Rahmoune Thileli, Elyasmine Hocine, Feriel Benmbarek, Berni Searle.
English; French; Arabic
Keywords: Contemporary Art; N4390-5098 Exhibitions; Africa